Assessing the Investment Climate for Rural Enterprises - Larson, Gunnar; Lamb, John; VanDer Meer, Cornelis (World Bank, Washington, DC, 2012)
The 2008 World Development Report identifies competition as an important variable of the rural investment climate. Competition triggers innovation and the productivity gains that drive economic growth, and with it the creation of jobs. Employment is generally the principal pathway that people have out of poverty. Fostering such competitive environments entails inducing the entry of local, mainly small-and-medium enterprises as well as the development of agribusinesses that enable small farmers, entrepreneurs, and investors to participate in expanding markets. The barriers to entry confronting prospective small rural enterprises include all the risks and costs and market failures characteristic of many rural economies, in addition to poor access to financial and public services, weak business skills, and extremely limited or non-existent information about what demand consists of in the non-local markets they hope to sell to. Improving the opportunities and incentives for rural firms to invest productively, expand, and bring on new workers should be a policy priority for governments, particularly given the prominence of policy, regulations, and enforcement in rural investors' perception of risk. Providing a sound, enabling policy environment is a vital role of the government and public sector and includes setting food quality and safety grades and standards and reliable contract enforcement. Such stable policy environments go very far in relieving investors' uncertainty over what governments will do next, what policies will be formulated, and how policies and regulations will be interpreted and enforced. This is a pressing concern among investors. Making policy formulation and enforcement more predictable can dramatically encourage investment (World Bank 2005).